AUTOMATEDSYSTEMOFTHEFLEETMANAGEMENTOFTHETRANSPORT COMPANY - Borisov, S. V. (Science and Transport Progress, 2004)
The paper reports the results of developing the automatic management system for railcars fleet of an expedition company. A special feature of the program is the information certificate that is added to the electronic technical certificate of the wagon.